Effects sintering temperature on mechanical properties of aluminium 5% Fly ash composite produced using hot pressing - Subarmono, Subarmono (2009)
This research aims to investigate mechanical properties of aluminium matrix composites reinforced with fly ash (AMC/fly ash) produced using hot isostatic pressing (HIP). Aluminium matrix composites (AMC) were prepared from aluminium fine powder as matrix and fly ash as reinforcement The amount of fly ash of 5% wt was added to the aluminium fine powder. It was then mixed using rotary mixer for 3 hr. The mixture was compacted using uniaxial pressing with a pressure of 100 MPa and it was followed hot isostatic pressed at various temperature of 525°C, 550°C and 575°C for 3 hours. Bending strength , Vickers hardness, wear resistance and density of the AMC were tested, and the micro structures were observed using SEM. The results show that the bending strength, Vickers hardness and wear resistance increase with increasing sintering temperature up to 50°C. Those properties are not significantly influenced on speciment sintered above 550°C. The bending strength, Vikers hardness, porosity and wear rate of specimens sintered at 550°C for 3hr are 77 MPa, 63 VHN, 2,6% and 0,03mg/(MPa.m), respectively